Marketing Analysis of Potato in Batu City - Muhammad Khoirul Aziz; Masahid Masahid; Badiatud Durroh (Tropical Plantation Journal, 2023)
Sumberbrantas village is one of the areas located in the highlands which is one of the potential for potato commodity development. The high potential of the region is also supported by the willingness of farmers to cultivate potatoes. The purpose of this study was to determine the marketing channel for potato commodities and the efficiency level of marketing institutions for potato commodities in Sumberbrantas Village, Bumiaji District, Batu City. This study uses the Cluster Random Sampling method. In this study only covers the city of Malang and Batu city. The samples that will be used as respondents in the study are 30 potato farmers, 2 collectors, and 4 retailers. Data analysis used descriptive analysis, marketing margin analysis and Farmer's Share analysis. The results of this study are farmers - collectors - retailers - consumers. The marketing margin value for each potato in this marketing channel is IDR 3,500. The share value or profit share is 90.76% and the cost share is 9.2% so it can be concluded that this marketing channel is logical because the profit share value obtained is greater than the cost share in the marketing channel. The average selling price received by farmers is 9,500/kg. the value of PS or the percentage of farmers' profits is 73.07% of the price at the consumer level, which is Rp. 13,000/kg.